Macro-Economic Consequences of Terrorism and Anti-Terrorism Expenditure on Economic Performance in Nigeria, 1980-2014 - Aiyedogbon, John Olucoris; Gugong, Benjamin Kumai; Anyanwu, Sarah Olanrewaju (SOSIOHUMANIKA, 2016)
ABSTRACT: The worldwide manifestation of terrorism has been evident in Africa, including Nigeria. With particular reference to Nigeria, the phenomenon has found expression in the emergence of Boko Haram insurgency. Since its advent, the sectarian insurgency has wrecked immense havoc in the country, especially by using explosives and firearms with gruesome fatal consequences. This paper focuses on macro-economic consequences of terrorism and counter terrorism expenditure on economic performance in Nigeria, over the period 1980â2014. The paper argued that due to attacks occasioned by terrorism and other criminal activities in Nigeria, many firms have either closed down or relocated to other countries. The objective of the study is to examine the impact of counter terrorism expenditure of the government and terrorist attacks on economic performance in Nigeria. The study finds that while impact of government expenditure in security on economic growth is positive and significant, the relationship between the later and terrorist attacks is negative. The paper recommended that the nation defense forces should be adequately equipped to urgently deal with the menace of insecurity in Nigeria. KEY WORD: Terrorism; Counter Terrorism Expenditure; Terrorist Attacks; Economic Performance; Nation-State of Nigeria.Â RESUME: âKonsekuensi Makro-Ekonomi tentang Terorisme dan Pengeluaran Kontra Terorisme terhadap Kinerja Ekonomi di Nigeria, 1980-2014â. Manifestasi global tentang terorisme telah terbukti di Afrika, termasuk Nigeria. Dengan merujuk khusus kepada Nigeria, fenomena itu telah diekspresikan dengan munculnya pemberontakan Boko Haram. Sejak kemunculannya, pemberontakan sektarian tersebut telah membuat malapetaka besar di negara Nigeria, terutama karena menggunakan bahan peledak dan senjata api dengan konsekuensi yang fatal mengerikan. Makalah ini memfokuskan pada konsekuensi makro-ekonomi tentang terorisme dan pengeluaran kontra terorisme terhadap kinerja ekonomi di Nigeria, selama periode 1980-2014. Makalah ini menyatakan bahwa karena serangan yang disebabkan oleh terorisme dan kegiatan kriminal lainnya di Nigeria, banyak perusahaan telah ditutup atau dipindahkan ke negara-negara lain. Tujuan penelitian ini adalah untuk menguji dampak serangan terorisme dan biaya untuk menangani terorisme dari pemerintah terhadap kinerja ekonomi di Nigeria. Penelitian ini menemukan bahwa sementara dampak pengeluaran dari pemerintah dalam keamanan terhadap pertumbuhan ekonomi itu bersifat positif dan signifikan, namun hubungannya kemudian dengan serangan teroris adalah negatif. Makalah ini merekomendasikan bahwa kekuatan pertahanan nasional harus dilengkapi secara memadai untuk segera menangani ancaman ketidakamanan di Nigeria.KATA KUNCI: Terorisme; Pengeluaran Kontra Terorisme; Serangan Teroris; Kinerja Ekonomi; Negara-Bangsa Nigeria.Â Â Â Â About the Authors: John Olucoris Aiyedogbon, Ph.D. is a Senior Lecturer at the Department of Economics, Faculty of Humanities, Social, and Management Sciences BU (Bingham University), Karu, Abuja, Nigeria. Benjamin Kumai Gugong, Ph.D. is a Senior Lecturer at the Department of Accounting, Faculty of Social and Management Sciences KSU (Kaduna State University), Nigeria. Sarah Olanrewaju Anyanwu, Ph.D. is a Professor of Development Economics and Head of the Department of Economics UA (University of Abuja) and also a Visiting Professor to other Universities in Nigeria. Corresponding authors are: johnaiyedogbon@gmail.com, bkgugong@yahoo.com, and sarahanyanwu@yahoo.comHow to cite this article? Aiyedogbon, John Olucoris, Benjamin Kumai Gugong & Sarah Olanrewaju Anyanwu. (2016). âMacro-Economic Consequences of Terrorism and Anti-Terrorism Expenditure on Economic Performance in Nigeria, 1980-2014â in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.9(1) May, pp.1-10. Bandung, Indonesia: Minda Masagi Press and UPI Bandung, ISSN 1979-0112. Chronicle of the article: Accepted (February 19, 2016); Revised (March 20, 2016); and Published (May 20, 2016).